Oppressors’ Defamation Methods In Confrontation Of The People Of Truth In The Story Of Fir’aun From The Noble Quran - Mohd Shafiee, Hamzah; Maged Ahmed Ali, Muthanna Al-Qaifi (2018)
Oppressors use different methods of expression when they confront the people of truth, depending on the realities and events they experience. One of the most important and influential methods is the so-called “defamation” used by the oppressors in order to reveal the people’s negative image, so that they would hated and avoided. They hide these methods from people and refuse to reveal the reality. Therefore, researcher intends to write this article, which aims to highlight the methods of “defamation” used by the oppressors in the story of Fir’aun (Pharaoh) in the Quran and the extent of its influence. The researcher has relied on descriptive analytical approach and the deductive approach. The study found that Fir’aun confronted Prophet Musa (AS) with different methods of defamation in order to influence the people. These kinds of defamation methods are prevalent in the present day, where the oppressors confront the people of truth. Nevertheless, there are differences in the types of these methods depending on time and place. It was found that these methods constitute a great obstacle to the people of truth and prevent them from reaching their desired goal. It was also revealed that following the oppressors makes people susceptible to the affliction in this world and the torment in the hereafter.